Ciliated Foregut Cyst of the Pancreas: Another Differential in the Diagnosis of Cystic Pancreatic Lesions - Vyas, Soumil; Luong, Tu Vinh; Yu, Dominic; Rahman, Sakhanat (JOP. Journal of the Pancreas, 2014)
Context With the more frequent use of cross sectional imaging, the detection of cystic pancreatic incidentalomas has become a relatively common entity. The commonest cystic incidentalomas are neoplastic. Pseudocysts are the most single common pathological entity. Foregut cystic lesions as a pathological entity are rare but mostly observed in the mediastinum. Ciliated foregut cysts of the pancreas are very rare and an extremely uncommon cause of a cystic lesion within the pancreas. Case report We present herewith an uncommon case of a large cystic lesion, confirmed as a ciliated foregut cyst on final histology arising from the body and tail of the pancreas. The lesion was very effectively treated with a laparoscopic distal pancreatectomy and splenectomy. Conclusion The rarity of the lesion makes the case worth reporting. Image: Distal pancreatectomy/splenectomy specimen.